Maintenance of maritime structures proceedings of a conference organized by the Institution of Civil Engineers and held in London on 13 October, 1977. (Institution of Civil Engineers, 1978)
Topics discussed in these papers include the organisation of the systematic underwater inspection and maintenance of offshore facilities, the present position of underwater welding, provides case histories of repairs to maritime structures, and highlights corrosion control for steel structures.